TESTING OF JANUARY EFFECT STOCK EXCHANGE IN JAKARTA (LQ 45 company case studies on the JSE) - Astut, Dina i; Legowo.,M.Si.,Akt, Drs. H.Herman (Accounting, 2009)
The biggest stock exchanges in Indonesia is the Jakarta Stock Exchange (JSE), which is also known by the name of its foreign Jakarta Stock Excange (JSX). Securities traded on the JSE are preferred shares (Preferred stock), shares of common stock (common stock), rights (rights), and convertible bonds (convertible bonds). Common shares dominate trading volume on the JSE. Based on the data that has been collected and analyzed from this study is that the return tends to fall in December and rose in January. For stock return obtained more meaningful for financial and trade sectors should investors buy shares in February, March, April, May, September, October, November, and December. Then sell these shares in January, June, July, August. Empirical evidence shows that the average stock return in February, March, April, May, September, October, November and December tend to be lower than in January, June, July, August tends to be higher. Based on the results of this study occurred in the January effect on the Jakarta Stock Exchange company that belongs to the group LQ 45 in the study period 2004-2006. With the January effect phenomenon occurred in the Jakarta Stock Exchange, it can be concluded if a capital market anomaly then have a capital market is efficient in the form of half-strength (semi-strong) and are not efficient in weak form. This study rejected a previous study Sukmawati and Herman (2001) which states that at the Jakarta Stock Exchange, although there are differences in stock returns in January are higher than in September but has no significant effect. The results of this study also shows that investors can earn higher returns by exploiting poal monthly returns that occurred in the Jakarta Stock Exchange. Keywords: January effect, Jakarta Stock Exchange, Return.